Immunomodulatory Effects Mediated by Dopamine - Rodrigo Arreola; Samantha Alvarez-Herrera; Gilberto Pérez-Sánchez; Enrique Becerril-Villanueva; Carlos Cruz-Fuentes; Enrique Octavio Flores-Gutierrez; María Eugenia Garcés-Alvarez; Dora Luz de la Cruz-Aguilera; Emilio Medina-Rivero; Gabriela Hurtado-Alvarado; Saray Quintero-Fabián; Lenin Pavón (Journal of Immunology Research)
Dopamine (DA), a neurotransmitter in the central nervous system (CNS), has modulatory functions at the systemic level. The peripheral and central nervous systems have independent dopaminergic system (DAS) that share mechanisms and molecular machinery. In the past century, experimental evidence has accumulated on the proteins knowledge that is involved in the synthesis, reuptake, and transportation of DA in leukocytes and the differential expression of the D1-like (D1R and D5R) and D2-like receptors (D2R, D3R, and D4R). The expression of these components depends on the state of cellular activation and the concentration and time of exposure to DA. Receptors that are expressed in leukocytes are linked to signaling pathways that are mediated by changes in cAMP concentration, which in turn triggers changes in phenotype and cellular function. According to the leukocyte lineage, the effects of DA are associated with such processes as respiratory burst, cytokine and antibody secretion, chemotaxis, apoptosis, and cytotoxicity. In clinical conditions such as schizophrenia, Parkinson disease, Tourette syndrome, and multiple sclerosis (MS), there are evident alterations during immune responses in leukocytes, in which changes in DA receptor density have been observed. Several groups have proposed that these findings are useful in establishing clinical status and clinical markers.